2015
DOI: 10.3389/fmed.2015.00076
|View full text |Cite
|
Sign up to set email alerts
|

Single-Dose Anti-CD138 Radioimmunotherapy: Bismuth-213 is More Efficient than Lutetium-177 for Treatment of Multiple Myeloma in a Preclinical Model

Abstract: ObjectivesRadioimmunotherapy (RIT) has emerged as a potential treatment option for multiple myeloma (MM). In humans, a dosimetry study recently showed the relevance of RIT using an antibody targeting the CD138 antigen. The therapeutic efficacy of RIT using an anti-CD138 antibody coupled to 213Bi, an α-emitter, was also demonstrated in a preclinical MM model. Since then, RIT with β-emitters has shown efficacy in treating hematologic cancer. In this paper, we investigate the therapeutic efficacy of RIT in the 5T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 46 publications
3
48
0
Order By: Relevance
“…24 Conjugation yields were high (75 ± 3% with [ 125 I]SIB and 77 ± 3% with [ 211 At]SAB) with good preservation of immunoreactivity (86 ± 2%).…”
Section: Resultsmentioning
confidence: 99%
“…24 Conjugation yields were high (75 ± 3% with [ 125 I]SIB and 77 ± 3% with [ 211 At]SAB) with good preservation of immunoreactivity (86 ± 2%).…”
Section: Resultsmentioning
confidence: 99%
“…The present work demonstrated the high targeted-tumor uptake of 64 Cu-TE2A-9E7.4 in MM tumor-bearing mice. Based on our experience with the B-B4 mAb [ 24 , 25 ], our group had developed this rat anti-mouse syndecan mAb (9E7.4, IgG2a κ isotype) that specifically recognizes the extracellular domain of mouse syndecan-1 [ 26 ]. This study showed that 64 Cu-TE2A-9E7.4 binds effectively to CD138 tumors and allows MM imaging in a syngeneic mouse model with high contrast.…”
Section: Discussionmentioning
confidence: 99%
“…The 9E7.4 mAb was produced by immunization of a rat with a 40-amino-acid peptide (GeneCust, Luxembourg) derived from the murine CD138 protein (aa 90–130) (GenBank: CAA80254.1). Its characterization was ensured within the team as previously described [ 26 ]. The isotype of this antibody is IgG2a,κ, and its binding specificity was around 1 × 10 −10 M.…”
Section: Methodsmentioning
confidence: 99%
“…178,179 Recent work has shown that coupling this antibody to radioactive isotopes significantly increased survival in animal models of MM. 179 The targeting of antigens and other cell-surface proteins in the treatment of cancers is rapidly expanding through the use of antibodydrug conjugates, which combine the specificity of a monoclonal antibody with a small anticancer drug molecule. Preclinical in vitro and in vivo work with these conjugates has demonstrated promise in the treatment of MM and other hematological cancers.…”
Section: Imids and Monoclonal Antibodiesmentioning
confidence: 99%